Kualitas Pelayanan Pembuatan Surat Keterangan Pindah Kependudukan Di Kantor Kelurahan Tatura Utara Kecamatan Palu Selatan Kota Palu - Sussanti Sussanti (Jurnal ADMINISTRATOR, 2021)
Based on the results of initial observations that researchers did, there were still liars committed by service officers at the North Tatura Village Office. And also the administrative service time is quite long, which is above 30 minutes. Whereas based on the Standard Operating Procedure (SOP) for administrative services in North Tatura Village, it states the requirements to make or improve population administration, then the community must complete it with a photocopy of family card, photocopy of proof of payment of PBB, old ID card for additions and transfer letter for those who move. no fees are charged with a service time of 10 to 15 minutes. The type of research used in this research is descriptive. The establishment of the Palu City Regional Regulation Number 8 of 2004 concerning the administration of the population of Palu City, the content in this Regional Regulation is also specifically concerning the National Population Identification Number (NIK) instead of the Resident Number for regional visits. The type of research used in this research is descriptive. In this study, the researcher was involved in the situation and setting of the phenomenon under study. In this study, interviews were conducted with informants consisting of the New Village Head, Secretary of the Village Head, Head of the Government Section, and the Community. The results of interviews with researchers and informants obtained are then presented in the form of discussions then explanations and explanations